NEUROPHYSIOLOGICAL EVIDENCE IN IDEA GENERATION: DIFFERENCES BETWEEN DESIGNERS AND ENGINEERS. (May 2020) - Colombo, S.; Mazza, A.; Montagna, F.; Ricci, R.; Dal Monte, O.; Cantamessa, M.
Abstract: The paper describes the rigorous implementation of a validated methodological experimental protocol to divergent and convergent thinking tasks occurring in Design by neurophysiological means (EEG and eye-tracking). EEG evidence confirms the findings coherently to the literature. Interesting is the confirmation of such results through eye-tracking ones, and further evidence emerged. In particular, neurophysiological results in idea generation differ between designers and engineers. This study was supported by a multidisciplinary team, both for the neuropsychological and data analysis aspects.